Determinants of Audit Fees and Non-audit Fees for Listed UK Companies - Zhu, Yan (2010)
This study mainly examines the characteristics of financial distress, earnings management, executive remuneration and low balling simultaneously determine audit and non-audit fees. Single-equation models are utilized in this research for both audit and non-audit fee models by using a sample of listed UK companies in FTSE for the period 2001-2010.